Design of bicycle-friendly intersections - Alaira, Zara Selyn A.
Bicycles are one of the best alternatives when it comes to saving economically and environmentally, two important aspects of civil engineering. They are efficient and useful for short-distance travels. People using bicycles save more on transportation costs in the long run while also promoting healthy living and lifestyle. Bicycles also offer environmental benefits, producing zero air pollution and minimal noise pollution. However, intersections, one of the vital facilities of the road network are generally designed to prioritize the motorized modes of transportation over the non-motorized modes, such as bicycles. This research project studied different guidelines on designing intersections accommodating bicycles. A set of criteria was established based on three issues: safety, comfort, and efficiency issues. Each criterion was defined by the problems of the intersection that fell under the different categories. Based on the set of criteria and the collected guidelines, intersections were assessed on their bicycle-friendliness level. Each intersection was re-designed to solve the issues. This was done by making sure that existing elements of the intersection abided by the standards, missing elements were installed, and parameters and signals were reconfigured. As an output, two ideal and general bicycle-friendly intersections, one for an unsignalized and another for a signalized intersection, were produced.